O papel dos grupos de apoio no compartilhamento da informação e do conhecimento nas avaliações das instituições de ensino superior privadas - Armando Sérgio de Aguiar Filho (2016)
The objective of this thesis is to analyze the practices of sharing information and knowledge in Higher Education Institutions Support Groups Private structures in its institutional reviews of processes to realize the existence of a dominant behavior. The work was developed from a literature search focusing on the collection and presentation of studies on information sharing channels and the knowledge, seeking to identify its correlates in the area of administration. In research we used quantitative qualitative mixed methodology study of multiple cases. The context of the research was the private higher education, developing case studies in seven institutions of the State of Minas Gerais and Federal District. Research has indicated considerations relevant to the understanding of the various approaches used in relation to the sharing of channels, as well as the common and different characteristics of these media and the impact on their dynamics, analyzed in different contexts, to assess and promote information services more adequate to meet the specific demands. The results of data collection with the seven Managers of Support Groups of institutions analyzed and forty-four participants of these groups showed strong evidence that, in fact, the sharing of knowledge generated in the Support Group contributes to the improvement of institutional evaluations processes.